Development of a laboratory tour guide robot - Kon, Wai Seng. (2010)
There are many variations of tour guide robots developed throughout the world, each with its own unique features. As tours occur frequently in the Robotics Research Centre of the Nayang Technological University, a project was undertaken to develop a laboratory tour guide robot. The laboratory your guide robot was implemented on the ATRV-Jr which is an existing robot in the Robotics Research Centre with path planning capabilities and a waypoint navigation system. A dialog-based application referred to as the Tour program was developed using Microsoft Foundation Class for the implementation of the laboratory tour guide robot. The Tour Program has a graphical user interface for the purposes of obtaining user input on the preferences for the tour and for the administrators to update information on the tour.